1988
DOI: 10.1111/j.1439-0434.1988.tb01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pH and the Production of Organic Acids During Colonization of Tomato Petioles by Botrytis cinerea

Abstract: After inoculation of petiole stumps of tomato plants with a tomato isolate of B. cinerea, a transition zone between water‐soaked and apparently healthy tissue became clearly visible. Hyphal colonization occurred up to approximately 2 mm beyond this zone. In the colonized tissue the pH values were lower than in the healthy tissue. In the region with most of the tips of the advancing hyphae, however, pH values were slightly, but consistently, higher. In the colonized tissue concentrations of oxalic, citric and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 18 publications
2
27
0
1
Order By: Relevance
“…First, a rise in pH during infection of either rice or barley, and a rise in pH together with ammonia production during fungal growth in vitro were monitored. Some plant pathogenic fungi like S. sclerotiorum and B. cinerea are known to acidify their environment during infection via the secretion of acids [15]. Others, like Alternaria alternata and several Colletotrichum species, tend to alkalinize the invaded plant tissues via the secretion of alkali like ammonia [33], [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a rise in pH during infection of either rice or barley, and a rise in pH together with ammonia production during fungal growth in vitro were monitored. Some plant pathogenic fungi like S. sclerotiorum and B. cinerea are known to acidify their environment during infection via the secretion of acids [15]. Others, like Alternaria alternata and several Colletotrichum species, tend to alkalinize the invaded plant tissues via the secretion of alkali like ammonia [33], [34].…”
Section: Discussionmentioning
confidence: 99%
“…One particular signal transduction pathway present in fungi relates to the sensing and adaptation to pH. As compared to other microorganisms, fungi are capable of growth and development over wide pH ranges, and several species, including plant pathogens, can modulate the pH of their environment by secreting acids or alkali [15], [16]. Thus far, a single pH-signaling pathway has been identified whose composition seems conserved throughout the fungal kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…The fungus acidifies its environment by secreting oxalic and citric acid (Verhoeff et al, 1988;Germeier et al, 1994;Manteau et al, 2003), presumably as part of its infection strategy (Germeier et al, 1994;Manteau et al, 2003;Prins et al, 2000;ten Have et al, 2002). There are numerous examples of the modulation of expression of genes encoding secreted enzymes in plantpathogenic fungi (Rollins & Dickman, 1998;St Leger et al, 1998;Wubben et al, 2000;Yakoby et al, 2000).…”
Section: B Cinerea Cultures Exclusively Contain Secreted Ap Activitymentioning
confidence: 99%
“…BcAP1 has an additional unique characteristic in that it does not contain a disulphide bridge. To remain properly folded and stable, the BcAP1 enzyme presumably resides extracellularly since this is the most acidic 'environment' for B. cinerea (Verhoeff et al, 1988;Germeier et al, 1994;Manteau et al, 2003).…”
Section: Features Of the Bcap Gene Familymentioning
confidence: 99%
“…It can infect different organs including cotyledons, leaves, stems, roots, flowers and fruits at different stages of their development. B. cinerea, like the closely related necrotrophic fungus S. sclerotiorum, uses an infection strategy based on the acidification of the ambient environment via the production of organic acids (oxalic or citric acids) (Verhoeff et al, 1988) and on the secretion of numerous cell-walldegrading enzymes, including proteases (Manteau et al, 2003). It has been reported that B. cinerea secretes several acidic proteases during pathogenesis.…”
Section: Introductionmentioning
confidence: 99%